THE DEVELOPMENT OF CHEMISTRY HANDOUT BASED ON UNITY OF SCIENCES PRINCIPLES FOR THE CHAPTER OF ACID AND BASE MATERIALS - Shofwunnada, Shofwunnada; Nirwana, Ratih Rizqi; Hakim, Fachri (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2018)
This research aims to produce a handout of chemitry based on the principle of unity of sciences to the material of acid and base. Unity of sciences is a paradihm that all sciences is united from Allah the Almighty. The subject of this research was students of XI MAN MAN Kendal, a school which supposes to have more concern of religion than regular school. This research used research and development approach. The handout was stated as very valid with the average validator score of 90%, readability test of 94% which means it does not need revision, and good responses of 80.41%. In conclusion, this handout is proper to enough to use in the learning process.